Analysis of Students' Ability to Answer Reading Assessments with High Level Thinking Skills (Hots) - Muti'ah, Anggi; Reflinda, Reflinda; Melani, Melyann; Eliza, Eliza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
AbstractThis research is motivated by concerns about students' low ability to answer reading assessments with higher-order thinking skills (HOTS). Most of the issues that arise indicate that students' skill abilities are still low, and some students are not ready to face contextual problems, reasoning, situations that require creativity, all of which commonly occur in HOTS. The purpose of this research is to deepen understanding of students' abilities in the aspects of analysis, evaluation, and creation, which are key components of HOTS. The study was conducted on 30 eighth-grade students at Madrasah Tsanawiyah Negeri 02 Pasaman Barat as a representation of the population. The instrument used was a reading test consisting of 20 multiple-choice questions that measure three components of HOTS: analyzing, evaluating, and creating. The test indicators were adopted from Bloom's Taxonomy and Anderson. The research results show that students' high-order thinking abilities in answering reading assessments are sufficient. It can be seen from the average scores obtained by students in the analyzing component (64.66), evaluating (72.85), and creating (61.39), with an overall average for all components (66.3) falling into the